Advokater och klienter i samtal om domar. Från intervjuer om uppfattad förståelse till ”lärande i interaktion” som metod för att studera begriplighet i text - Sörlin, Marie (Klart språk i Norden, 2014)
Through their work, lawyers are privy to certain insights into how their clients understand and react to verdicts – insights that may prove useful in the plain language work with court texts. In my presentation I first described the results from a smaller interview-based study I conducted on this theme at the request of the so called Förtroendeutredningen (the Swedish Government Official Report on trust, SOU 2008:106, “Increased trust in courts of law – strategies and suggestions”). I then discussed the pros and cons of using interviews with lawyers to capture clients’ understanding of court texts, and outlined a possible continuance study based on my results. In the article “Lawyers and clients discussing verdicts” I follow the same disposition, but look at the possible follow-up study in greater detail. Could the intelligibility of court texts be investigated by analyzing the discussions between lawyer and client from a learning by interaction-perspective?